„Żyje się tylko chwilę” — Did Halina Poświatowska Really Die Young? - Marczak, Ewa Joanna (Starość i młodość w literaturze i kulturze, 2016)
The poet Halina Poświatowska for the most of her 32-years life overcame limitations associated withacquiring a mitral valve defect. She spent many months in hospitals, nursing homes and in the familyhome. In spite of common opinion she was not living for a very short time indeed when taking into account the state of cardiac surgery in the middle of the last century. The length of her life as a woman with serious heart defect, which caused additional complications in the functioning of the circulatory system, can not be compared to the life length of healthy people.